Post-Natal Indonesian Garut Sheep Performance Fed with Sorghum-Indigofera-Mixed Feed and Stimulated with Pregnant Mare Serum Gonadotropin Hormone - Somanjaya, Rachmat; Fuah, Asnath Maria; Rahayu, Sri; Abdullah, Luki; Setiadi, Mohamad Agus (Universitas Airlangga, 2025)
This study aimed to determine the effect of sorghum-indigofera (SI) mixed feed and pregnant mare serum gonadotropin (PMSG) hormone stimulation on ewe’s reproductive performance and Garut lamb’s pre-weaning growth. Twenty-eight multiparous Garut ewes were included into four treatment groups (2 ´ 2) with a factorial-Completely Randomized Design (CRD). The first factors were the types of feed local forage (LF) and SI, while the second factor was PMSG hormone stimulations (with and without PMSG stimulation). Synchronized estrous used twice injections with PGF2α, 11 days apart, and 500 IU PMSG was adminstrated at the second PGF2α injection intramuscularly. The observed variables included ewes' performance after parturition and post-natal lamb's growth. The obtained data were analyzed by multivarians of analysis (MANOVA) with α = 0.05 and continued with Tukey's Test. The result showed that feeding ewes with SI without PMSG stimulation resulted in the highest number of pregnancies, litter size, and lactation compared to other treatments. Feed type and PMSG stimulation factors has no any interaction effect (p > 0.05) on birth weight, weaning weight, and milk production. However, birth weight and milk production were affected (p < 0.05) by the feed, while weaning weight was affected (p < 0.05) by the PMSG stimulation. The fastest lamb growth rate was found in the groups of ewes fed by SI without PMSG stimulation (120 g/head/day). It can be concluded that SI could improve the ewe’s reproductive performance and the post-natal growth of Garut lambs. Meanwhile, the PMSG hormone could beneficially with sorghum-indigofera mixed feed.